2017
DOI: 10.1111/tri.12974
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial wellbeing after living kidney donation - a longitudinal, prospective study

Abstract: Living kidney donation (LKD) has become routine practice across the world as the gold standard treatment of end-stage renal failure. Whilst the physical risks and harms of LKD surgery are well documented, relatively little is known about psychosocial outcomes. The aim of this study was to determine whether it was possible to quantify the psychosocial impact of LKD. A prospective longitudinal study of 93 living kidney donors was performed. Data were collected preoperatively, and 3 and 12 months after donation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 50 publications
2
39
0
1
Order By: Relevance
“…Prospective studies in living kidney donors have shown small decreases in health-related quality of life (HRQoL) shortly after donation, generally returning to baseline in the longer term [1][2][3]. Also, HRQoL scores after donation mostly return to the level of general population norms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies in living kidney donors have shown small decreases in health-related quality of life (HRQoL) shortly after donation, generally returning to baseline in the longer term [1][2][3]. Also, HRQoL scores after donation mostly return to the level of general population norms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Biller-Andorno [18] Trotz allem berichten nahezu alle Lebendnierenspender (98 %), sie würden die Spende erneut durchführen, wenn sie könnten. In ähnlichen Studien finden sich diesbezüglich Raten zwischen 89-94 % [11,15,19,20]. Auch wenn die Mehrheit der Lebendspen-der eine Belastung des körperlichen oder psychischen Befindens durch die Lebendspende verneint, berichtet dennoch ein relativ hoher Anteil diesbezüglich Beschwerden.…”
Section: Beziehung Zwischen Spender Und Empfängerunclassified
“…The current evidence indicates that when living donors are appropriately screened and selected, long‐term physical and psychological morbidity is limited, and there is no impact on life span . Recent studies in living kidney donors have shown that there may be a small increased relative risk of end‐stage renal failure when compared to matched healthy nondonors, however, the absolute risk remains low .…”
Section: Introductionmentioning
confidence: 99%